2017
DOI: 10.21037/cdt.2017.10.08
|View full text |Cite
|
Sign up to set email alerts
|

Deep venous thrombosis in pregnancy: incidence, pathogenesis and endovascular management

Abstract: Deep venous thrombosis (DVT) during pregnancy is associated with high mortality, morbidity, and costs. Pulmonary embolism (PE), its most feared complication, is the leading cause of maternal death in the developed world. DVT can also result in long-term complications that include postthrombotic syndrome (PTS) adding to its morbidity. Women are up to 5 times more likely to develop DVT when pregnant. The current standard of care for this condition is anticoagulation. This review discusses the epidemiology, patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 62 publications
3
138
0
8
Order By: Relevance
“…Nevertheless, in developed nations, the leading cause of maternal death is thromboembolic disease [19][20][21] . Thrombotic events during pregnancy, including maternal DVT(deep venous thrombosis) and pregnancy-related cerebral venous sinus thrombosis, are responsible for increasing levels of maternal mortality worldwide [22,23] . Previous studies have shown that this hypercoagulability is exacerbated in pregnant women with GDM [4,24,25] and that there is a significantly higher frequency of DVT in pregnant women with type 1 diabetes mellitus [26] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in developed nations, the leading cause of maternal death is thromboembolic disease [19][20][21] . Thrombotic events during pregnancy, including maternal DVT(deep venous thrombosis) and pregnancy-related cerebral venous sinus thrombosis, are responsible for increasing levels of maternal mortality worldwide [22,23] . Previous studies have shown that this hypercoagulability is exacerbated in pregnant women with GDM [4,24,25] and that there is a significantly higher frequency of DVT in pregnant women with type 1 diabetes mellitus [26] .…”
Section: Discussionmentioning
confidence: 99%
“…During the analysis, the data were anonymized, and therefore the requirement for informed consent was waived. To avoid recruitment bias, we collected consecutive data from all pregnant women awaiting delivery, but not yet in labor, in the Obstetrics department of our hospital from 23 October to 23 November 2018. After the exclusion of 18 individuals for the reasons given below, 182 women were included in the analysis, who were classified as having GDM or not having GDM (the GDM group and the NGDM group).…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…8,9 Previous studies have reported that diabetes, hypertension, cerebral vascular disease (CVA), heart failure, cancers, pregnancy, lower leg fracture and major surgery are associated with risk of VTE. [10][11][12][13][14] Prophylactic anticoagulants for reducing the risk of VTE may be considered for acutely ill patients. 15 However, a discrepancy has been observed between the incidence rates of VTE reported in Taiwan and in Western countries.…”
Section: Chung and Linmentioning
confidence: 99%
“…Deep vein thrombosis (DVT) and pulmonary embolism (PE) constitute VTE, which remains a major contributor to 30‐day and 1‐year case fatality rates . Previous studies have reported that diabetes, hypertension, cerebral vascular disease (CVA), heart failure, cancers, pregnancy, lower leg fracture and major surgery are associated with risk of VTE . Prophylactic anticoagulants for reducing the risk of VTE may be considered for acutely ill patients .…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that the physiological changes in pregnancy induce a prothrombotic environment which increases the risk of thrombosis (4)(5)(6). In addition, certain patient populations are already at increased risk of thrombosis including those with mechanical heart valves (MHVs) and previous VTE (7).…”
Section: Chapter 1: Backgroundmentioning
confidence: 99%